Nanomedicine-based cancer immunotherapy: a bibliometric analysis of research progress and prospects - Chen, Chaofan; Yuan, Pengfei; Zhang, Zhiyun (Frontiers in Immunology, 2024)
Despite the increasing number of studies on nanomedicine-based cancer immunotherapy, the overall research trends in this field remain inadequately characterized. This study aims to evaluate the research trends and hotspots in nanomedicine-based cancer immunotherapy through a bibliometric analysis. As of March 31, 2024, relevant publications were retrieved from the Web of Science Core Collection. Analytical tools including VOSviewer, CiteSpace, and an online bibliometric analysis platform were employed. A total of 5,180 publications were analyzed. The study reveals geographical disparities in research output, with China and the United States being the leading contributors. Institutionally,